2019
DOI: 10.1115/1.4045397
|View full text |Cite
|
Sign up to set email alerts
|

An Expanding Cavity Model for Indentation Analysis of Shape Memory Alloys

Abstract: The mechanical and functional responses of shape memory alloys (SMAs), which are often used in small volume applications, can be evaluated using instrumented indentation tests. However, deciphering the indentation test results in SMAs can be complicated due to the combined effects of the non-uniform state of stress underneath the indenter and stress-induced phase transformation. To address this issue, an expanding cavity model (ECM) applicable to spherical indentation of SMAs is developed in this work based on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Lawn et al [72] suggested that the widely-used expanding cavity models for describing the deformation fields underneath indenter are then no longer valid when a material undergoes densification by compaction within the immediate contact zone of a sharp indenter. (This is also true when phase transformations occur underneath the indenter [73,74].) This is because of the intense hydrostatic compressive stresses that render the volume of the indentation to be more readily accommodated within the compaction zone, diminishing the intensity of any residual stresses.…”
Section: Crack Initiation and Cracking Resistancementioning
confidence: 99%
“…Lawn et al [72] suggested that the widely-used expanding cavity models for describing the deformation fields underneath indenter are then no longer valid when a material undergoes densification by compaction within the immediate contact zone of a sharp indenter. (This is also true when phase transformations occur underneath the indenter [73,74].) This is because of the intense hydrostatic compressive stresses that render the volume of the indentation to be more readily accommodated within the compaction zone, diminishing the intensity of any residual stresses.…”
Section: Crack Initiation and Cracking Resistancementioning
confidence: 99%
“…In this section, approximate equations representing the mean contact pressure and transformed zone size evolution are developed, based on ECM, following the approach proposed by Johnson [42] and Narasimhan [43] for elastic-plastic solids and Anuja et al [38] for pressure insensitive SMAs. As a first step towards this end, a pressure sensitive SMA sphere, initially in the A phase, of radius b having a cavity with radius a (a < b) subjected to pressure p c is analyzed and expressions for stresses and displacements are obtained.…”
Section: Expanding Cavity Modelmentioning
confidence: 99%
“…However, owing to the complex stress state present beneath the indenter and the concurrent occurence of plastic yielding and SIMT, interpretation of the results is not straightforward. Hence, the spherical indentation response of SMAs has been studied using a combination of experiments and simulations [24][25][26][29][30][31][32][33][34][35][36][37][38]. One of the most important challenges involved with indentation is to develop correlations between bulk properties like elastic modulus, transformation stress and strain, yield strength, etc and nano-indentation test data such as load-depth curves, hardness and depth recovery ratio recorded using small samples.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations